ANALYSIS OF CENTRIFUGAL SCREW MIXER OPERATION APPLYING MULTIPLE REGRESSION METHOD WHEN OBTAINING BAKERВЂ™S FLOUR MIX TO PRODUCE BAKERY PRODUCTS FOR SPORTSMEN - Borodulin D.M.; Nevskaya E.V.; Kiselev D.I.; Shlelenko L.A.; Potapova M.N. (Техника и технология пищевых производств)
Currently, many regions of the Russian Federation including the Kemerovo region face serious problems with food products quality. Foods having a low content of essential macro- and micronutrients fill the grocery market. Therefore, enrichment of foods with amino acids, omega-3 and omega-6 polyunsaturated fatty acids, vitamins, minerals, etc. is an urgent task. A centrifugal screw mixer for bulk materials with selected rational operation parameters used for the enrichment of flour mix with vitamins and other beneficial substances was developed in the laboratory of the department «Technological design of food production» at Kemerovo Technological Institute of Food Industry (University). Analyzing the mixing process applying a multiple regression method, we have found that «Regression response surface» most accurately describes the process and that the number of screw flights and the frequency of the operation element rotation influence the quality of mixing significantly. Investigations on the optimization of the qualitative and quantitative ingredient composition of baker’s flour mix have been done at Research Institute of Baking Industry. Biological value of bread baked from the developed flour mix was analyzed, and it was found that its amino acid score had increased from 9 to 43% compared to the control additive-free sample. The shelf life for baker’s flour mix has been established.